Deterministic versus stochastic seasonal fractional integration and structural breaks - Guglielmo Maria Caporale; Juncal Cunado; Luis A. Gil-Alana (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper considers a general model which allows for both deterministic and stochastic forms of seasonality, including fractional (stationary and nonstationary) orders of integration, and also incorporating endogenously determined structural breaks. Monte Carlo analysis shows that the suggested procedure performs well even in small samples, accurately capturing the seasonal properties of the series, and correctly detecting the break date. As an illustration, the model is estimated for four different US series (output, consumption, imports and exports). The results suggest that the seasonal patterns of these variables have changed over time: specifically, in the second subsample the systematic component of seasonality becomes insignificant, whilst the degree of persistence increases.
Keywords: C22; 330; Saisonbereinigung; Zeitreihenanalyse; Stochastischer Prozess; Strukturbruch; Theorie; Schätzung; Konjunktur; USA